Flexible prices and leverage - D’Acunto, Francesco; Liu, Ryan; Pflueger, Carolin; Weber, Michael (Journal of Financial Economics, 2018)
The frequency with which firms adjust output prices helps explain persistent differences in capital structure across firms. Unconditionally, the most flexible-price firms have a 19% higher long-term leverage ratio than the most sticky-price firms, controlling for known determinants of capital structure. Sticky-price firms increased leverage more than flexible-price firms following the staggered implementation of bank deregulation across states and over time, which we use in a difference-in-differences strategy. Firms’ frequency of price adjustment did not change around the deregulation.